2022
DOI: 10.3389/fchem.2022.1042709
|View full text |Cite
|
Sign up to set email alerts
|

Interlink between solubility, structure, surface and thermodynamics in the ThO2(s, hyd)–H2O(l) system

Abstract: The impact of temperature on a freshly precipitated ThO2(am, hyd) solid phase was investigated using a combination of undersaturation solubility experiments and a multi-method approach for the characterization of the solid phase. XRD and EXAFS confirm that ageing of ThO2(am, hyd) at T = 80°C promotes a significant increase of the particle size and crystallinity. TG-DTA and XPS support that the ageing process is accompanied by an important decrease in the number of hydration waters/hydroxide groups in the origi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
0
0
Order By: Relevance
“…This hypothesis is in line with previous studies that have revealed that the dissolution process of cerium dioxide and other less soluble substances is not representative of the bulk phase, but is rather controlled by the surface processes of a few monolayers of the corresponding oxide. 28,29,[60][61][62] After chemical precipitation, a significant amount of hydroxyl groups is present on the surface of CeO 2 particles. Some studies have proposed considering particles of metal dioxides obtained from solutions as being particles with a core/shell structure, or even proposed judging the hydroxylated surface layer as a microphase.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is in line with previous studies that have revealed that the dissolution process of cerium dioxide and other less soluble substances is not representative of the bulk phase, but is rather controlled by the surface processes of a few monolayers of the corresponding oxide. 28,29,[60][61][62] After chemical precipitation, a significant amount of hydroxyl groups is present on the surface of CeO 2 particles. Some studies have proposed considering particles of metal dioxides obtained from solutions as being particles with a core/shell structure, or even proposed judging the hydroxylated surface layer as a microphase.…”
Section: Discussionmentioning
confidence: 99%